Mathematical Critical Thinking Profiles of Seventh-Grade Students in Solving Fraction Problems within Realistic Mathematics Education Contexts - Neli Neli; Siti Suprihatiningsih (Jurnal Didactical Mathematics, 2026)
This study investigates seventh-grade students’ mathematical critical thinking profiles in solving fraction problems involving different denominators within Realistic Mathematics Education (RME) contexts. A qualitative multiple-case descriptive design was employed involving 18 students who completed contextual essay-based mathematical tasks, with six students purposively selected for in-depth semi-structured interviews representing high-, medium-, and low-ability categories. Data were collected through written tasks and interview protocols developed according to Ennis’s five critical thinking indicators: interpretation, analysis, evaluation, inference, and explanation. Data analysis followed an interactive qualitative approach involving data reduction, data display, and conclusion verification. The findings revealed substantial variation in students’ mathematical critical thinking across indicators and ability categories. High-level students demonstrated relatively systematic and coherent reasoning processes, whereas medium- and low-level students exhibited fragmented reasoning characterized by procedural uncertainty and conceptual difficulties. Interpretation emerged as the most accessible indicator, while inference and explanation represented the most challenging dimensions. Additive misconception was identified as the most dominant conceptual difficulty, particularly among low-level students, indicating broader weaknesses in fraction understanding rather than isolated procedural errors. Furthermore, the findings suggest that mathematical critical thinking indicators function as interconnected dimensions, where difficulties occurring during earlier reasoning stages frequently coincided with limitations in subsequent processes. This study contributes to mathematics education literature by providing a multidimensional understanding of students’ mathematical critical thinking through the integration of written responses and interview data. The findings highlight the importance of instructional practices emphasizing conceptual understanding, reflective reasoning, and meaningful mathematical contexts.